Tetra‐primer amplification refractory mutation system (ARMS) PCR used to detect 3’UTR rs1948 mutation in CHRNB4 - Anggi Laksmita Dewi; Dewi Kartikawati Paramita; Jajah Fachiroh (Universitas Gadjah Mada, 2022)
Rs1948 A>G is a single nucleotide variation (SNV) in the 3’‐UTR of CHRNB4. Genotyping the synonymous CHRNB4 rs1948 may be useful in identifying a lung cancer susceptibility gene. The study aimed to develop a simple and easy tetra‐primer amplification refractory mutation system (ARMS PCR) for CHRNB4 rs1948. The following steps were taken to optimize tetra‐primer ARMS PCR: 1) determining the gene sequence and position of a single mutation; 2) developing outer and inner primers; 3) amplification of target gene fragments via PCR using an outer primer; 4) genotyping PCR product using Sanger sequencing; 5) determining the optimal annealing temperature and PCR cycle; 6) determining optimal outer and inner primer ratio; and 7) testing the reproducibility of the PCR program and final validation with Sanger sequencing. Genotype (PCR result) was visualized with 3% agarose gel electrophoresis. Optimum condition was determined as annealing temperature of 64.8 ºC and 35 cycles, outer and inner primer ratio of 1:6, and DNA volume of 3 µL. Sanger sequencing confirmed the results of the tetra‐primer ARMS PCR and it was shown that ARMS PCR was able to identify three different variants of CHRNB4 rs1948.